Oral manifestations of lipoid proteinosis: A case report and literature review - S.M. Ravi Prakash; Sankalp Verma; M.N. Sumalatha; Sayan Chattopadhyay (Elsevier, 2013)
Lipoid proteinosis is an uncommon autosomal recessive metabolic disorder that presents in early life with hoarseness and pox-like acneiform scars involving the skin and mucous membranes. Previous studies have attributed the prevalence of lipoid proteinosis to consanguineous parents. This paper reports a classical case of lipoid proteinosis with oral manifestations but without a history of consanguinity. Keywords: Acneiform scars, Consanguinity, Hoarseness, Lipoid proteinosis, Monoliform blepharosis